Pengaruh Kedalaman Lubang Perkolasi Terhadap Daya Resap Tanah Berpasir (Sandy Soil) dan Tanah Berlempung (Loamy Soil) - Putri Nur Hayati; Tubtas Bagyono; Adib Suyanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2010)
One of the alternatives for overcoming the excessive run-off and groundwater deposit problems is by infiltrating water beneath the ground. The infiltration process depends on soil textures, such as loamy soil has small porosity, while sandy soil has higher porosity. The study is aimed to reveal the effect of the depth of percolation holes between sandy and loamy soils towards their pene-trating capacity. This was a pre-experimental research employed post test only design, and located at Sukunan Village, Gamping, Sleman Regency for the sandy, and at Gedongan Sumberagung Village, Moyudan, Sleman Regency for the loamy one. Results of the study show percolation rate average of sandy soil for 50, 100 and 150 cm hole depth variation were 0.593 cm/minute, 1.565 cm/minute, and 2.529 cm/minute respectively. The p-value obtained from the one-way Anova test was <0,001, which means that the penetrating capacity among the depth variation was significantly different. Results for loamy soil for the same depth variation were 0.396 cm/minute, 0.582 cm/minute, and 0.914 cm/minute, respectively, with the corresponding p-value was <0,001 as well. The sub-sequent LSD test produced p-values of <0,001 for all depth pairs comparison, as well as the result of t-test for comparing the difference between sandy and loamy soils. Based on the results it can be concluded that the highest percolation rate is for sandy soil at 150 cm hole depth.